Raising Helpful Children: Exploring Conflict Between Goals and Practices in Euro-Heritage Socialization of Helping - Fairchild, Luc (Frontiers in Psychology, 2021)
Helping others benefits both helper and helpee and is the basis for societal structures that promote collective well-being. Many parents Using a White, European-heritage ‘Constellation of practices’ (UWEC), recognize the importance of raising a child who helps others. Yet UWEC children seem to take initiative to help with household work less, and in ways that benefit others less, than other children globally. It is important for future researchers to explore the phenomenon of many UWEC parents using practices that work against their explicit goals, and suggestions are made for future work, including better integration of cross-cultural evidence in developmental psychological study design. Better integrating evidence and exploring this conflict further would greatly advance our understanding of the socialization of helping, and may elucidate how much change is possible and advisable regarding how best to raise children to think and act in other-oriented ways that are beneficial for all.